A EXECUÇÃO IMEDIATA DE PENA APLICADA PELO TRIBUNAL DO JÚRI: ESVAZIAMENTO DA PRESUNÇÃO DE INOCÊNCIA? - TAVARES, HORTÊNCIA DE VASCONCELOS (2025)
This paper analyzes the thesis established in the judgment of Theme 1,068 (HC 135340/SC), of the Supreme Federal Court and its (in) inconsistency with the principle of presumption of innocence and other constitutional guarantees arising therefrom. The topic is relevant, since its debate brings to light the conflict between the presumption of innocence and the immediate application of punishment by the Jury Court. In view of the problem presented, the objective is to analyze the normative structure of the Jury Court and its constitutional conformation; to critically reflect on the amendment of art. 492, I, ‘’e’’ of the Code of Criminal Procedure and its impact on the practical implementation of the principle of presumption of innocence in the criminal execution phase and, finally, to verify whether the current jurisprudential orientation, notably that established in Theme 1,068, meets a constitutional interpretation and whether it has systemic coherence with the norms that make up the national legal system and whether it is compatible with decisions previously issued on the matter within the scope of the STF. In achieving the proposed objectives, the hypothetical deductive methodology applied to bibliographic research and jurisprudential analysis was used. The results indicated that the current understanding of the STF regarding the constitutionality of art. 492, I, ‘’e’’ of the Code of Criminal Procedure does not have adequate legal support, since it conflicts with the precedents of the Court itself and directly conflicts with fundamental principles, especially the presumption of innocence, since the thesis prevailed “The sovereignty of the verdicts of the Jury Court authorizes the immediate execution of the sentence imposed by the jury, regardless of the total sentence applied.